To solve

-2x+3y =8 .......(1)and

3x-y = -5...........(2).

From the second equation, we get y = 3x+5, which substitute in eq (1).

-2x+3(3x+5) = 8

-2x+9x-15 = 8

7x+15 =8

7x=8-15= -7

x = -7/7 = -1.

From the 1st equation, -2x+3y = 9 , -2(-1) +3y = 8

3y = 8-2 = 6

y = 6/3 =2

So x= -1 and y = 2.

Fr

We'll solve the system using the elimination method.

We'll note the equations of the system as:

-2x+3y = 8 (1)

3x-y = -5 (2)

We'll multiply (2) by 3:

3*(3x-y) = -5*3

9x - 3y = -15 (3)

We'll add (3) to (1):

9x - 3y - 2x + 3y= -15+8

We'll eliminate like terms:

7x = -7

We'll divide by -7:

x = -1

We'll substitute the value of x into (2):

3x-y = -5

-3- y = -5

We'll add 3 both sides:

-y = -5+3

-y = -2

y = 2

**The solution of the system is: {(-1 , 2)}.**

The system of equations -2x+3y=8 and 3x-y=-5 has to be solved.

Using the equation 3x - y = -5 express y in terms of x. 3x - y = -5 gives y = 3x + 5

Substitute y = 3x + 5 in the equation -2x + 3y = 8

-2x + 3(3x + 5) = 8

-2x + 9x + 15 = 8

7x = -7

x = -1

As y = 3x + 5 = -3 + 5 = 2

The solution of the given set of equations is x = -1 and y = 2